Tinjauan Atas Pengendalian Internal Persediaan Bahan Baku Pada PT ABP - Andreas Bagus Primadani; Evi Yuniarti; Damayanti Damayanti (Politeknik Negeri Lampung, 2022)
The purpose of this study was to find out how the internal control of raw material inventory carried out by PT ABP was in accordance with the components of internal control according to the committee of sponsoring organizations. The types of data used were primary and secondary data. The data analysis method used was qualitative method. The results of the study shows that the internal control of raw material inventory at PT ABP is in accordance with all the components of internal control, namely the control environment, control activities, risk assessment, information and communication, and supervision.